In good taste : a contemporary approach to cooking. - Gielisse, Victor; Kimbrough, Mary E.; Gielisse, Kathryn G. (Upper Saddle River, NJ : Prentice Hall, 1999)
Philosophy on food and wine and the effect on Lifestyles. Recipe for a Healthfu Cuisine. Nutritional Cooking. The Recipes. Industry Issues.
Keywords: Nutrition; Cookery; Cookery; Nutrition